Gut microbiota are differentially correlated with blood pressure status in African American collegiate athletes: A pilot study - Taylor Hogue; Jarrad Hampton‐Marcell; Ian M. Carroll; Troy Purdom; Heather Colleran; TJ Exford; Michael Brown; Marc D. Cook (Physiological Reports, 2024)
Abstract Hypertension (HTN) is common among athletes and the most recent epidemiologic data reports that cardiovascular (CV) sudden death is significantly greater in African Americans (AAs). Gut microbial dysbiosis (a poorly diverse stool microbial profile) has been associated with HTN in sedentary people but microbial characteristics of athletes with HTN are unknown. Our purpose was to differentiate microbiome characteristics associated with BP status in AA collegiate athletes. Thirty AA collegiate athletes were stratified by normal BP (systolic BP (SBP) ≤130 mmHg; n = 15) and HTN (SBP ≥130 mmHg; n = 15). 16S rRNA gene sequencing was performed on stool samples to identify microbes at the genus level. We did not observe any significant differences in alpha diversity, but beta diversity was different between groups. Principal coordinate analysis was significantly different (PERMANOVA, p < 0.05, R = 0.235) between groups. Spearman rank correlations showed a significant (p < 0.05) correlation between systolic BP and abundances for Adlercreutzia (R = 0.64), Coprococcus (R = 0.49), Granulicatella (R = 0.63), and Veillonella (R = 0.41). Gut microbial characteristics were associated with differentially abundant microbial genus' and BP status. These results will direct future studies to define the functions of these microbes associated with BP in athletes.